FROM THE METHOD OF EDUCATIONAL GAMES IN MATHEMATICS LESSONS IN PRIMARY SCHOOL ADVANTAGES OF USE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is an in-depth and effective teaching of mathematics for the formation of young people in primary education as mature, talented and gifted personnel in the future and provides theoretical information in the form of recommendations for the use of modern, advanced teaching methods and practical application of concepts.